Calculating the earth's radius: emulating Eratostenes (Revista de Investigaciones Universidad del Quindío, 2023)
2,255 years ago, the great Greek mathematician, astronomer, and geographer Eratosthenes of Cyrene, with sticks, shadows, mathematics, astronomy, and imagination, calculated the radius of the Earth. For this reason, several cities in the world, Bogotá (Colombia), Buenos Aires (Argentina), Naples (Italy), Úbeda (Spain), and Sao Paulo (Brazil), participated in the project to measure the radius of the Earth according to the method of Eratosthenes in ancient times. Each participating city had to take data on the location and the angle of the shadow cast by a vertical pole between September 22 and October 4, 2021. Once these data had been collected, the mean distance of the radius of the Land. The results obtained were: 6,205 km for Bogotá, 6,365,983 km for Buenos Aires, 6,392,121 km for Úbeda, 6,590,238 km for Naples and 6,596,579 km for Sao Paulo. We can infer from the result of the experience, that it allowed the participating cities to have a close collaboration, to a scientific test that put them in contact, through Astronomy
Keywords: Astronomy; Earth's Radius; SARS-CoV-2; Noon; solar angle